Novel α-tubulin mutation disrupts neural development and tubulin proteostasis - Hanson, Martin G. (Dev Biol, 2015)
Mutations in the microtubule cytoskeleton are linked to cognitive and locomotor defects during development, and neurodegeneration in adults. How these mutations impact microtubules, and how this alters function at the level of neurons is an important area of investigation. Using a forward genetic screen in mice, we identified a missense mutation in Tuba1a α-tubulin that disrupts cortical and motor neuron development. Homozygous mutant mice exhibit cortical dysgenesis reminiscent of human tubulinopathies. Motor neurons fail to innervate target muscles in the limbs and show synapse defects at proximal targets. To directly examine effects on tubulin function, we created analogous mutations in the α-tubulin isotypes in budding yeast. These mutations sensitize yeast cells to microtubule stresses including depolymerizing drugs and low temperatures. Furthermore, we find that mutant α-tubulin is depleted from the cell lysate and from microtubules, thereby altering ratios of α-tubulin isotypes. Tubulin-binding cofactors suppress the effects of the mutation, indicating an important role for these cofactors in regulating the quality of the α-tubulin pool. Together, our results give new insights into the functions of Tuba1a, mechanisms for regulating tubulin proteostasis, and how compromising these may lead to neural defects.